2022
DOI: 10.46827/ejes.v9i6.4306
|View full text |Cite
|
Sign up to set email alerts
|

Teaching and Learning Challenges in the Pandemic Era of Covid-19

Abstract: COVID-19 pandemic has driven the education system to shift from face-to-face learning to a home learning system through online learning. This sudden change has worried teachers, parents and students all over the world. Various studies have been done to study the implementation of online learning, however, there are a little number of studies among school teachers, especially in Malaysia. Thus, this study aimed to explore teachers’ perspectives on the challenges of home learning and their commendations. A quali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 22 publications
(28 reference statements)
0
0
0
Order By: Relevance
“…Other than that, the research finding was also consistent with study by Zain et al (2022), as well as Ainul and Ishak (2021) in Malaysia, where not every household had enough computers, laptops, or mobile phones for their children. In some cases, only the parents had access to the gadgets, preventing the children from learning during the day.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Other than that, the research finding was also consistent with study by Zain et al (2022), as well as Ainul and Ishak (2021) in Malaysia, where not every household had enough computers, laptops, or mobile phones for their children. In some cases, only the parents had access to the gadgets, preventing the children from learning during the day.…”
Section: Discussionsupporting
confidence: 88%
“…Apart from that, Zain et al (2022) in their interview sessions among 20 teachers in Seremban District, Negeri Sembilan revealed that the online learning medium availability among them was a challenge. The government decided to continue education through online learning following the implementation of MCO.…”
Section: Online Learning Accessibilitymentioning
confidence: 99%